Global Bifurcation for a Class of Lotka-Volterra Competitive Systems (Journal of Nonlinear Modeling and Analysis, 2024)
For a class of Lotka-Volterra competitive systems including bothdiffusion and advection, a global bifurcation result of positive steady statesis established via a bifurcation approach. Also, the phenomenon of multiplepositive steady states is discussed.